Representation in civil law - Зейкан, Ярослав Павлович; Ігнатенко, Всеволод Владиславович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article analyzes the current legislation of Ukraine, judicial practice and theoretical positions on the definition and essence institute representation in civil processes. Due to the recent changes made to the Constitution of Ukraine, which gradually introduces "monopoly of lawyers" to represent people in courts, it is important to decide on the actual purpose of the Institute representative, its concept and essence. According to Art. 38 CCP party, third party, a person under the law protects the rights, freedoms or interests of others as well as applicants and other interested parties in separate proceedings (except for cases of adoption) can participate in a civil case in person or through a representative. The term "representation" can be viewed in three ways: as an Institute of Civil Procedure; a relationship with representative; activity as representative. The views of scientists on this issue can be divided into two basic concepts: "action (activity)" and "relationship", depending on the answer to the question of what is to represent the activity or legal relationship within which these activities occur. Describing Institute representation in civil proceedings should identify inherent characteristics: - members can only be individuals who have full civil capacity and under 18 years of age (except in special cases); - the representative can only be a natural person; - organizations that do not have legal personality, always involved in the process through representatives; - the activity of a legal person is considered as well as the activities of the representative. The object of the legal relationship between the representative and the court should consider protection, (in separate proceedings) violated, unrecognized or disputed rights, freedoms and interests of individuals and legal entities, state interests in civil proceedings.